2019
DOI: 10.1136/bmjebm-2018-111142
|View full text |Cite
|
Sign up to set email alerts
|

Teaching evidence-based medicine application: transformative concepts of information mastery that foster evidence-informed decision-making

Abstract: Information mastery is an approach to applying the methods of evidence-based medicine to everyday practice. The aim of this research is to describe concepts identified by clinicians attending a 3-day course on applied evidence-based medicine that led to ‘transformative learning’, in which they experienced a deep, structural shift in the basic premises of thought, feelings and actions in their approach to making medical decisions. We used a qualitative approach to capture the lived experience of 12 current and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Specifically, Sokol and colleagues showed that formal classes on evidence-based medicine can lead to transformative learning when the learner masters such threshold concepts as 'uncertainty is an aspect of medical decisions, but steps can be taken to proceed confidently'. [45] Our results show similar effects, since in the learning conversations we observed trainees trying to master threshold concepts related to using EBM in daily clinical practice. Troublesome signs were apparent, since trainees described their need for help if they felt unsure or were unable to apply evidence in a straightforward manner.…”
Section: Threshold Conceptssupporting
confidence: 76%
“…Specifically, Sokol and colleagues showed that formal classes on evidence-based medicine can lead to transformative learning when the learner masters such threshold concepts as 'uncertainty is an aspect of medical decisions, but steps can be taken to proceed confidently'. [45] Our results show similar effects, since in the learning conversations we observed trainees trying to master threshold concepts related to using EBM in daily clinical practice. Troublesome signs were apparent, since trainees described their need for help if they felt unsure or were unable to apply evidence in a straightforward manner.…”
Section: Threshold Conceptssupporting
confidence: 76%
“…leader, namely providing motivation to students so that they can easily understand the lesson (4). maintaining whether learning has achieved the goals in learning or not Mastery of Information and Communication Technology (ICT) is very important in the 21st century, mastery of computers to process, access and provide information both individually and in groups is an important requirement in this digital era (Sokol et al, 2019;Stockless et al, 2018;Tulung, 2020). the development of Information and Communication Technology (ICT) is very fast if you don't learn it well, you might be left behind, so you have to learn technology, almost everyone has used it Information and Communication Technology (ICT) such as mobile phones and the internet, so developments in the use of technology must be developed following the benefits of using Information and Communication Technology (ICT) in the world of education (1).…”
Section: Introductionmentioning
confidence: 99%